The Papers of Jefferson Davis : 1880-1889 - Davis, Jefferson, 1808-1889 (Book collections on Project MUSE., 2015)
The final volume of The Papers of Jefferson Davis follows the former president of the Confederacy through the completion of his two monumental works on the history of the Confederate States of America. In the first, The Rise and Fall of the Confederate Government (1881), Davis sought to recast the Confederacy as a just and moral nation that was constitutionally correct in standing up for its rights. Himself the subject of heated debates about why the Confederacy lost, Davis also used the book to castigate Confederate government and military officials who he believed had failed the cause. Later, A Short History of the Confederate States (1890) attempted to burnish the image of the former Confederacy and to refute accusations of intentional mistreatment of Union prisoners. While completing these books, Davis attended and spoke at numerous Confederate memorial services and monument dedications, all the while waging a bitter feud with two of his former top generals-Joseph E. Johnston and P. G. T. Beauregard-over the reasons for the fall of the Confederacy. In late 1889, having returned to New Orleans from a trip to his plantation, Brierfield, Davis succumbed to pneumonia. His funeral procession attracted an estimated 150,000 mourners, a testament to the lasting popularity of the Confederacy's only president. In volume 14 of The Papers of Jefferson Davis, the editors have drawn from over one hundred manuscript repositories and private collections, in addition to numerous published sources, to offer a compelling portrait of Davis over the last decade of his life.